Factors affecting emergency preparedness competency of public health inspectors: a cross-sectional study in northeastern China. Issue 1 (2nd January 2014) - Ning, Ning; Kang, Zheng; Jiao, Mingli; Hao, Yanhua; Gao, Lijun; Sun, Hong; Wu, Qunhong
Abstract : Objectives: To determine the emergency preparedness competency specific to public health inspectors (PHIs), preparedness limitations and needs of the workforce, as well as to identify important factors that affect the preparedness competency of PHIs. Setting: Cross-sectional survey was conducted in Heilongjiang, a province in northeastern China. Participants: A questionnaire was administered to a sample of 368 PHIs from 17 public health inspection agencies, chosen by stratified cluster sampling strategy. 9 PHIs and 6 agency's leaders were invited to participate in an in-depth interview. Outcome measures: Self-rated preparedness competency in quantitative study was measured. Multivariate logistic regression model was used to test the associations between individual determinants and self-rated preparedness competency. Key themes relating to preparedness competency of PHIs in qualitative study were analysed. Results: Although 82% of PHIs highly rated their general preparedness competency, there were significant differences among the assessment on specific domains of their competency. Comparing with attitude, the domains of skills and knowledge tend to be lower (p=0.000). Awareness on one's own responsibilities regarding emergency response work was identified as the most important factor associated with preparedness competency (adjusted OR=6.33, 95% CI 3.30 to 12.16). Lack of explicit national job requirements, overlapping responsibilities and poor collaboration among agencies, together with poor knowledge and skills level of personnel, led to an ambiguity of responsibility, and hindered the preparedness competency enhancement of PHIs furthermore. Conclusions: Ambiguity responsibility in emergency response is still a prominent issue that hinders the further improvement on the preparedness competency for PHIs' in China. Intensified capacity-building activities targeting at individuals' weakness in specific knowledge and skills are urgently needed; in addition, capacity building at policy and system level as well as agency levels is of equal importance.